Perebutan Pengaruh Politik di Daerah Khusus Jakarta: Analisis Konflik Kepentingan Antara Elit Nasional dan Lokal Dalam Pemilihan Gubernur Tahun 2024 - Abdul Aziz Hamdi; Pujo Widodo; Eko G Samudro; Rachmat Setiawibawa; Arifuddin Uksan (CV. Rayyan Dwi Bharata, 2025)
The 2024 Jakarta gubernatorial election highlights the ongoing power struggle between national and local elites, reflecting broader political dynamics in Indonesia. As the capital city, Jakarta holds strategic importance, making its leadership contest not only a regional but also a national concern. The conflict between these two elite groups arises from differences in political interests, where national elites prioritize political stability and party dominance, while local elites focus on policies directly impacting Jakarta residents. This study aims to analyze the key factors that intensify this conflict and examine its impact on the electoral process and policy-making. Using a qualitative research approach with a literature review method, this study identifies four major drivers of conflict: divergent political agendas, national political interventions, identity politics, and communication gaps between elites. The findings indicate that these conflicts significantly affect candidate selection, campaign strategies, and governance after the election. Additionally, political polarization fueled by identity-based narratives has led to declining voter participation, increased invalid ballots, and eroding public trust in democracy. The study suggests that electoral reforms, increased transparency in political processes, and better coordination between national and local authorities are essential to mitigating elite conflicts and fostering a more democratic and representative electoral system in Jakarta.